Assessment of genetic diversity in balangir sheep breed by microsatellite DNA profiling - Rekha Sharma; Sonika Ahalawat; A K Pandey (Journal of Livestock Biodiversity, 2025)
Balangir, one of the important sheep breeds of Odisha state was investigated genetically utilizing microsatellite markers. Markers were selected on the guidelines of FAO’s DADIS (Domestic Animal Diversity Information System) MoDAD programme. The number of alleles, its frequencies, heterozygosities and heterozygote deficiency were estimated. A total number of 103 alleles were detected across nineteen microsatellite markers. Observed number of alleles varied from 2.0 to 9.0 with the mean of 5.421±1.774 which is higher than mean expected number of allele (3.360±1.118). The observed heterozygosity in the population varied from 0.239 to 0.714 with the mean of 0.495±0.098. Balangir sheep possesses sufficient genetic variation and thus has scope for the improvement.